Kebijakan Pendaftaran Elektronik: Perspektif Regulasi, Teknologi, dan Aksesibilitas - Mujiburohman, Dian Aries (Journal of Infrastructure Policy and Management, 2025)
This study examines the electronic land registration policy as a reform measure in land services in Indonesia. Through Minister of ATR/BPN Regulation Number 3 of 2023, the land administration system has begun to transition from a manual to a digital format to improve efficiency, transparency, and data security. Although this system offers numerous benefits, its implementation in the field still faces several obstacles, including limited internet access, a lack of technological understanding, and the public’s reliance on physical documents. This situation demonstrates that the success of an electronic system depends not only on the readiness of technology and regulations but also on how easily the public can access and utilize it. This article presents a more comprehensive approach by promoting synergy among policymakers, technology service providers, and the broader community. If all parties are actively involved, the electronic land registration system will not only be an administrative change but also a tool to strengthen land rights and improve the quality of public services.